2021
DOI: 10.3390/app11167323
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anatomy Education Method Using a Spatial Reality Display Capable of Stereoscopic Imaging with the Naked Eye

Abstract: Several efforts have been made to use virtual reality (VR) and augmented reality (AR) for medical and dental education and surgical support. The current methods still require users to wear devices such as a head-mounted display (HMD) and smart glasses, which pose challenges in hygiene management and long-term use. Additionally, it is necessary to measure the user’s inter-pupillary distance and to reflect it in the device settings each time to accurately display 3D images. This setting is difficult for daily us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Il serait judicieux d'inclure d'autres systèmes dans nos investigations, tels que des écrans avec des lunettes 3D ou des casques intégrant des vidéos en 2D. Une étude comparative entre quatre outils différents pourrait permettre d'analyser spécifiquement les effets potentiels de la vidéo 3D et de l'immersion [19]. De même, il serait intéressant d'évaluer l'apport de l'immersion sur d'autres types de contenu, tels que ceux présentant un caractère gestuel plus important, comme les sutures.…”
Section: Limites Et Travaux Futursunclassified
“…Il serait judicieux d'inclure d'autres systèmes dans nos investigations, tels que des écrans avec des lunettes 3D ou des casques intégrant des vidéos en 2D. Une étude comparative entre quatre outils différents pourrait permettre d'analyser spécifiquement les effets potentiels de la vidéo 3D et de l'immersion [19]. De même, il serait intéressant d'évaluer l'apport de l'immersion sur d'autres types de contenu, tels que ceux présentant un caractère gestuel plus important, comme les sutures.…”
Section: Limites Et Travaux Futursunclassified
“…Early works proposed holography in augmenting medical and anatomical education [153,154]. Several attempts for multiview autostereoscopic display utilization in medicine were carried out, including the implementation of a software for interacting with 3D medical models in real time [155], the 3D visualization of real captured surgical videos [156], neurosurgical reviews [157], an educational application for head and neck anatomy [158], and interactive 3D torso anatomy [159]. In a recent attempt to use autostereoscopic displays, specifically the 8-inch Looking Glass Portrait display [160], King's College London (KCL) implemented an online platform, namely Virtual Anatomy and Histology (VAH), targeted for anatomical teaching by means of 3D visualization of medical models and medical scans [161].…”
Section: Higher Educationmentioning
confidence: 99%
“…In a recent attempt to use autostereoscopic displays, specifically the 8-inch Looking Glass Portrait display [160], King's College London (KCL) implemented an online platform, namely Virtual Anatomy and Histology (VAH), targeted for anatomical teaching by means of 3D visualization of medical models and medical scans [161]. Furthermore, Itamiya et al [158] developed an autostereoscopic viewer that takes as input 2D CT, MRI, and CBCT images, and outputs the corresponding 3D model.…”
Section: Higher Educationmentioning
confidence: 99%
“…No studies have discussed the accuracy of 3D-CG models observed with AR devices within close range, which are required in clinical dentistry [14]. Although SRDs are beginning to be used in medical and dental education, their accuracies have not been compared with that of HMD [15]. Although SRD is beginning to be used in medical and dental education, its accuracy has not been verified [16].…”
Section: Figurementioning
confidence: 99%